Escaping Japan - Guanren, Blai, author.
1 online resource (320 pages)
Keywords: "The idea that Japan is a socially homogenous, uniform society has been increasingly challenged in recent years. This book takes the resulting view further by highlighting how Japan, far from singular or monolithic, is socially and culturally complex. It engages with particular life situations, exploring the extent to which personal experiences and lifestyle choices influence this contemporary multifaceted nation-state. Adopting a theoretically engaged ethnographic approach, and considering a range of "escapes" both physical and metaphorical, this book provides a rich picture of the fusions and fissures that comprise Japan and Japaneseness today."--Provided by publisher.